Cognitive control dysfunction and abnormal frontal cortex activation in stimulant drug users and their biological siblings - Smith, D G (Nature Publishing Group, 2013)
Cognitive and neural abnormalities are known to accompany chronic drug abuse, with impairments in cognition and changes in cortical structure seen in stimulant-dependent individuals. However, premorbid differences have also been observed in the brains and behavior of individuals at risk for substance abuse, before they develop dependence. Endophenotype research has emerged as a useful method for assessing preclinical traits that may be risk factors for pathology by studying patient populations and their undiagnosed first-degree relatives. This study used the color-word Stroop task to assess executive functioning in stimulant-dependent individuals, their unaffected biological siblings and unrelated healthy control volunteers using a functional magnetic resonance imaging paradigm. Both the stimulant-dependent and sibling participants demonstrated impairments in cognitive control and processing speed on the task, registering significantly longer response latencies. However, the two groups generated very different neural responses, with the sibling participants exhibiting a significant decrease in activation in the inferior frontal gyrus compared with both stimulant-dependent individuals and control participants. Both target groups also demonstrated a decrease in hemispheric laterality throughout the task, exhibiting a disproportionate increase in right hemispheric activation, which was associated with their behavioral inefficiencies. These findings not only suggest a possible risk factor for stimulant abuse of poor inhibitory control and cortical inefficiency but they also demonstrate possible adaptations in the brains of stimulant users.